ALKBH5 ALLEVIATES HYPOXIA POSTCONDITIONING INJURY IN d-GALACTOSE–INDUCED SENESCENT CARDIOMYOCYTES BY REGULATING STAT3. Issue 1 (8th January 2023) - Zhang, Xuan; Li, Feixiang; Ma, Ji; Zhang, Xiaobei; Yin, Yiqing
ABSTRACT: Ischemic postconditioning (I/Post) reduces I/R injury by activating endogenous cardioprotection mechanisms, such as the JAK/signal transducer and activator of transcription 3 (STAT3) and PI3K/Akt pathways, which offer a traditional approach to myocardial protection. According to a previous study, cardioprotection by I/Post may be lost in aged mice, and in our previous research, hypoxic postconditioning (H/Post) lacked a protective effect in senescent cardiomyocytes, which was associated with low expression of long noncoding RNA H19. The N6-methyladenosine (m 6 A) modification is a dynamic and reversible process that has been confirmed to play a role in cardiovascular diseases. However, the mechanisms of m 6 A modification in myocardial I/Post remain to be explored. Neonatal cardiomyocytes were isolated from 2-day-old Sprague-Dawley rats, and senescence was induced by d -galactose, followed by stimulation of hypoxia-reoxygenation and H/Post. Hypoxic injury was evaluated by cell viability and the Bcl-2/Bax protein ratio. Total m 6 A levels were measured using a colorimetric m 6 A RNA Methylation Quantification Kit, and the m 6 A modified and differentially expressed mRNA was determined by MeRIP (methylated RNA immunoprecipitation). We found that H/Post increased m 6 A methylation and decreased RNA mA demethylase alkB homolog 5 (ALKBH5) expression in aged cardiomyocytes. Furthermore, ALKBH5 knockdown exacerbated injury following H/Post in senescent cardiomyocytes. In addition, ALKBH5 regulated STAT3 expression by mediating its m 6 A modification and long noncoding RNA H19/miR-124-3p. ALKBH5 also alleviated the H/Post injury induced by the low expression of STAT3 in senescent cardiomyocytes.